Changes in the European Union definition for endocrine disruptors: how many molecules remain a cause for concern? The example of crop protection products used in agriculture in France in the six last decades - Roger, Cloé; Paul, Adèle; Fort, Emmanuel; Lamouroux, Céline; Samal, Areejit; Spinosi, Johan; Charbotel, Barbara (Frontiers in Public Health, 2024)
Background The endocrine-disrupting effects of phytopharmaceutical active substances (PAS) on human health are a public health concern. The CIPATOX-PE database, created in 2018, listed the PAS authorized in France between 1961 and 2014 presenting endocrine-disrupting effects for humans according to data from official international organizations. Since the creation of CIPATOX-PE, European regulations have changed, and new initiatives identifying substances with endocrine-disrupting effects have been implemented and new PAS have been licensed. Objectives The study aimed to update the CIPATOX-PE database by considering new 2018 European endocrine-disrupting effect identification criteria as well as the new PAS authorized on the market in France since 2015. Methods The endocrine-disrupting effect assessment of PAS from five international governmental and non-governmental initiatives was reviewed, and levels of evidence were retained by these initiatives for eighteen endocrine target organs. Results The synthesis of the identified endocrine-disrupting effects allowed to assign an endocrine-disrupting effect level of concern for 241 PAS among 980 authorized in France between 1961 and 2021. Thus, according to the updated CIPATOX-PE data, 44 PAS (18.3%) had an endocrine-disrupting effect classified as “high concern,” 133 PAS (55.2%) “concern,” and 64 PAS (26.6%) “unknown effect” in the current state of knowledge. In the study, 42 PAS with an endocrine-disrupting effect of “high concern” are similarly classified in CIPATOX-PE-2018 and 2021, and 2 new PAS were identified as having an endocrine-disrupting effect of “high concern” in the update, and both were previously classified with an endocrine-disrupting effect of “concern” in CIPATOX-PE-2018. Finally, a PAS was identified as having an endocrine-disrupting effect of “high concern” in CIPATOX-PE-2018 but is now classified as a PAS not investigated for endocrine-disrupting effects in CIPATOX-PE-2021. The endocrine target organs associated with the largest number of PAS with an endocrine-disrupting effect of “high concern” is the reproductive system with 31 PAS. This is followed by the thyroid with 25 PAS and the hypothalamic–pituitary axis (excluding the gonadotropic axis) with 5 PAS. Discussion The proposed endocrine-disrupting effect indicator, which is not a regulatory classification, can be used as an epidemiological tool for occupational risks and surveillance.